(untitled) (World Economics and Finance Bulletin, 2023)
The research seeks to investigate the (GVC) and identify the activities required to manufacture environmentally friendly green products beginning with green R&D and ending with green reverse supplies as well as assisting the Industrial enterprises management in the recycling of production waste and achieving cleaner production quality and cost-effective equipment. And the research concluded a set of conclusions the primary one of which is that the use of the (GVC) and cleaner production reduces emissions waste generated increases operational efficiency preserves Industrial enterprises resources reduces waste disposal costs and creates new investment opportunities.